Timp2-modified gelatinhydroxyphenylpropionic acid hydrogels reverse enhanced scleral recovery and suppress myopia development in mice - Kaiqi Liu; Ting Li; Lingwen Gu; Zhenyu Jiang; Jing Jiang; Xi Yang; Yang Zhou; Xiao Feng; Qianqian Gong; Lihua Zhao; Yiming Chen; Chao Yang; et al. (Materials Today Bio, 2025)
A novel therapeutic strategy for form deprivation myopia (FDM) involving Timp2-modified scleral stem cells (SSCTimp2) embedded in gelatin-hydroxyphenylpropionic acid (Gtn-HPA) hydrogel was investigated. Transcriptome and single-cell RNA sequencing analyses identified Timp2 as a crucial factor in FDM progression due to its reduced expression in FDM sclera. The developed SSCTimp2-Gtn-HPA hydrogel composite demonstrated excellent biocompatibility, rapid gelation, and degradation properties. In vitro studies showed that SSCTimp2-GH promoted human scleral fibroblast (HSF) proliferation, inhibited apoptosis, and prevented differentiation. In vivo experiments in mice showed that SSCTimp2-GH effectively regulated ocular parameters, facilitated scleral recovery, and improved FDM conditions. These results highlight the potential of SSCTimp2-GH as a promising therapeutic approach for myopia treatment by enhancing scleral recovery.